Re-evaluation of websites from burn centers in Austria, Germany and Switzerland - Benedikt, Stefan; Tapking, Christian (Burns, 2019)
Introduction Websites serve as information and communication platforms; hence, they are important tools for the self-promotion of hospitals. In 2010, Selig et al. evaluated the online presence of burn centers in Germany, Austria, and Switzerland based on 37 quality criteria. This study aimed to re-evaluate these websites to assess their development over the past 6.5 years. Materials and methods Websites of the German-speaking burn centers were re-evaluated according to criteria previously described by Selig et al. Particular attention was paid to specific information on burns. Additionally, the implementation of social media platforms was investigated. Results There was an overall increase in the quality of information published on websites. There was a considerable improvement recorded, especially in the categories of “teaching” and “patient care.” However, burn-specific information was found to be still sparse. Over 50% of the hospitals were present on social media. Conclusions Although the quality of information published on German-speaking burn center websites increased, they must be further developed, especially regarding burn-related information. Moreover, a clear structure and design could prevent long searches and facilitate an easier flow of information. The interface from websites and social media platforms appear to be an important tool for up-to-date self-promotion.